2004
DOI: 10.1179/030192304225019315
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of ladle teeming process

Abstract: In continuous casting, the molten steel is poured from the ladle to the tundish through a nozzle located at the bottom of the ladle. This process, however, must be stopped before the ladle is completely emptied to avoid slag carryover to the tundish. The amount of steel that remains unteemed in the ladle is usually significant, so steel plants are highly interested in studying different ways to improve the process. In the present work, experimental studies using water models and numerical simulations have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…(1)), which will lead to the formation of a two-phase funnel shaped interface through the liquid. The drain sink has been analyzed thoroughly by many authors 1,[3][4][5][6][7][8] and some details about previous publications can be found in Table 1 (2) where Q cr is the critical volumetric outflow rate, H cr is the liquid bath height and r 1 and r 2 is density of primary phase 1 and supernatant phase 2. This relationship has been slightly modified (for example multiplied with an empirical constant) by other authors and is reported to give good agreement when comparing the predictions to experimental data.…”
Section: Prediction and Disarming Of Drain Sink Formation During Unstmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)), which will lead to the formation of a two-phase funnel shaped interface through the liquid. The drain sink has been analyzed thoroughly by many authors 1,[3][4][5][6][7][8] and some details about previous publications can be found in Table 1 (2) where Q cr is the critical volumetric outflow rate, H cr is the liquid bath height and r 1 and r 2 is density of primary phase 1 and supernatant phase 2. This relationship has been slightly modified (for example multiplied with an empirical constant) by other authors and is reported to give good agreement when comparing the predictions to experimental data.…”
Section: Prediction and Disarming Of Drain Sink Formation During Unstmentioning
confidence: 99%
“…Furthermore, it has also been suggested that drain sink is the only of the two phenomena that occur during steel making. 4) In order to understand the drain sink, some simple calculations based on hydrodynamic principles can be done leading to Eq. (1):…”
Section: Previous Studiesmentioning
confidence: 99%
“…On the other hand, hand, a drain sink is characterized by the radial flow and develops in the last stage of the teeming process, when less liquid steel is left in the ladle. A drain sink is always present at the end of the process and takes place when the bath height of the steel is approximately equal to the nozzle diameter [4,6,16]. Several researchers claim that there was no vortex formation and slag carry-over was caused by drain sink in the teeming ladle [4,8], while more researchers reported that vortex was formed prior to the drain sink formation [1][2][3]7,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for the sake of cleaner steel, improved yield, and higher production, the onset of slag carry-over should be stalled as long as possible during ladle teeming. According to the literature [1][2][3][4][5], two different mechanisms can lead to slag carry-over in teeming ladle: vortex or drain sink. Vortex is characterized by high tangential velocities in the neighborhood of the tapping hole, and can develop even with a high bath height of steel in the teeming ladle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation